ADVANCING SUSTAINABLE AGRICULTURE THROUGH NANO-FERTILIZERS ANALYZING SOIL HEALTH AND CROP PRODUCTIVITY IN TROPICAL ECOSYSTEMS - Rahmawati Rahmawati; Siri Lek; Ton Kiat (Yayasan Adra Karima Hubbi, 2026)
Sustainable rice production in tropical ecosystems is constrained by low nitrogen-use efficiency, nutrient losses, declining soil quality, and increasing dependence on conventional fertilizers. This study aimed to evaluate the effects of nano-nitrogen fertilizer on soil health, nitrogen efficiency, and rice productivity under tropical field conditions. A randomized complete block design was implemented with six treatments: no nitrogen, 100% conventional urea, and nano-nitrogen fertilizer applied at 25%, 50%, 75%, and 100% of the recommended nitrogen rate, each replicated four times. Crop growth, chlorophyll content, nitrogen uptake, yield components, grain yield, agronomic efficiency, and selected physical, chemical, and biological soil indicators were analyzed using analysis of variance, post hoc comparisons, correlation, and regression. Results showed that the 75% nano-nitrogen treatment produced the highest grain yield, reaching 7.24 t ha?1, and exceeded full-rate conventional urea while improving productive tillers, chlorophyll status, nitrogen uptake, microbial biomass, urease activity, organic carbon, and aggregate stability. The 100% nano-nitrogen rate increased nitrogen uptake but provided no additional yield advantage, indicating a nonlinear response. The study concludes that optimized nano-nitrogen application can reduce fertilizer demand while improving rice productivity and soil functioning, although multi-season environmental and safety assessments remain necessary before widespread adoption across diverse tropical production environments.